Transcript profiling of sucrose synthase genes involved in sucrose metabolism among four carrot (Daucus carota L.) cultivars reveals distinct patterns - Yan-Jun Liu; Guang-Long Wang; Jing Ma; Zhi-Sheng Xu; Feng Wang; Ai-Sheng Xiong (BMC Plant Biology, 2018)
Abstract Background Carrot which contains lots of nutrients has a large demand around the world. The soluble sugar content in fleshy root of carrot directly influences its taste and quality. Sucrose, as an important member of soluble sugar, is the main product of photosynthesis in higher plants and it plays pivotal roles in physiological processes including energy supply, signal transduction, transcriptional regulation, starch and cellulose synthesis, and stress tolerance. Sucrose synthase is a key enzyme involved in sucrose metabolism and is closely related to sucrose content. However, the molecular mechanism involved in sucrose metabolism in carrot has lagged behind. Results Here, carrot roots of five developmental stages from four carrot cultivars were collected, and the contents of soluble sugar and sucrose in different stages and cultivars were surveyed. Three DcSus genes (DcSus1, DcSus2, and DcSus3), with lengths of 2427 bp, 2454 bp and 2628 bp, respectively, were identified and cloned in carrot. Phylogenetic analysis from the deduced amino acid sequences suggested that three DcSus were clustered into three distinct groups (SUSI, II and III). Results of enzymatic profiles demonstrated that the DcSus activities showed decrease trends during taproot development. Correlation analysis indicated that the DcSus activity showed negative correlation with soluble sugar content and strong negative correlation with sucrose concentration. Quantitative real-time PCR analysis showed that the expression profiles of the DcSus genes are significantly different in carrot tissues (root, leaf blade, and petiole), and the expression levels of the DcSus genes in the leaf blade were much higher than that in the root and petiole. The expression profiles of DcSus genes showed strong negative correlation with both sucrose content and soluble sugar content. Conclusions During carrot root development, the soluble sugar content and sucrose content showed increasing trends, while DcSus activities had persisting declinations, which may be due to the decreasing expression levels of genes encoding sucrose synthase. Our data demonstrate that synthesis of sucrose in carrot tissue is closely related with DcSus genes. The results from our study would not only provide effective insights of sucrose metabolism in carrot, but also are beneficial for biologists to improve carrot quality.